Gram-scale preparation of negative-type liquid crystals with a CF2CF2-carbocycle unit via an improved short-step synthetic protocol - Kumon, Tatsuya; Hashishita, Shohei; Kida, Takumi; Yamada, Shigeyuki; Ishihara, Takashi; Konno, Tsutomu (Beilstein Journal of Organic Chemistry, 2018)
Herein, we demonstrate an improved short-step protocol for the synthesis of multicyclic molecules having a CF2CF2-containing cyclohexadiene or cyclohexane framework in a mesogenic structure. These molecules are promising candidates for vertical alignment (VA)-mode liquid crystal (LC) display devices owing to their large negative dielectric constant. The tetrafluorinated multicyclic molecules were successfully obtained in only five or six reaction steps without the need for special handling techniques, as is generally required for thermally unstable organometallic species, representing a reduction of three reaction steps. The improved short-step synthetic protocol was also amenable to the multigram preparation of these promising molecules, which may contribute significantly to the development of novel negative-type LC molecules containing CF2CF2 carbocycles.
Keywords: gram-scale preparation; liquid crystals; short-step preparation; tetrafluorinated cyclohexadiene; tetrafluorinated cyclohexane

(untitled) - Charpentier, J.; Früh, N.; Togni, A. (Chem. Rev., 2015)

(untitled) - Campbell, M. G.; Ritter, T. (Chem. Rev., 2015)

(untitled) - Ni, C.; Hu, M.; Hu, J. (Chem. Rev., 2015)

(untitled) - Zhou, Y.; Wang, J.; Gu, Z.; Wang, S.; Zhu, W.; Aceña, J. L.; Soloshonok, V. A.; Izawa, K.; Liu, H. (Chem. Rev., 2016)

(untitled) - Ni, C.; Hu, J. (Chem. Soc. Rev., 2016)

(untitled) - O'Hagan, D. (Chem. Soc. Rev., 2008)

(untitled) - Konno, T. (Synlett, 2014)

Advances in Organic Synthesis, Modern Organofluorine Chemistry–Synthetic Aspects - Konno, T.; Ishihara, T. (Bentham Science Publishers, Ltd., 2006)

Fluorine-Containing Synthons - Konno, T.; Ishiahra, T. (A New Aspect of Fluoroalkylated Acetylenes: Synthesis and Applications—Hydrometallation and Carbometallation, 2005)

(untitled) - Kirsch, P. (J. Fluorine Chem., 2015)

(untitled) - Hird, M. (Chem. Soc. Rev., 2007)

(untitled) - Yamada, S.; Hashishita, S.; Asai, T.; Ishihara, T.; Konno, T. (Org. Biomol. Chem., 2017)

(untitled) - Yamada, S.; Hashishita, S.; Konishi, H.; Nishi, Y.; Kubota, T.; Asai, T.; Ishihara, T.; Konno, T. (J. Fluorine Chem., 2017)

(untitled) - Bonnac, L.; Lee, S. E.; Giuffredi, G. T.; Elphick, L. M.; Anderson, A. A.; Child, E. S.; Mann, D. J.; Gouverneur, V. (Org. Biomol. Chem., 2010)

(untitled) - Timofte, R. S.; Linclau, B. (Org. Lett., 2008)

(untitled) - Boydell, A. J.; Vinader, V.; Linclau, B. (Angew. Chem., Int. Ed., 2004)

(untitled) - Kaneko, S.; Yamazaki, T.; Kitazume, T. (J. Org. Chem., 1993)

(untitled) - Pierce, O. R.; Kane, T. G. (J. Am. Chem. Soc., 1954)

(untitled) - Amoah, E.; Dieter, R. K. (J. Org. Chem., 2017)

(untitled) - Pace, V.; Castoldi, L.; Hoyos, P.; Sinisterra, J. V.; Pregnolato, M.; Sánchez-Montero, J. M. (Tetrahedron, 2011)

(untitled) - Liu, H.-J.; Shia, K.-S.; Shang, X.; Zhu, B.-Y. (Tetrahedron, 1999)

(untitled) - Vougioukalakis, G. C.; Grubbs, R. H. (Chem. Rev., 2010)

(untitled) - Nolan, S. P.; Clavier, H. (Chem. Soc. Rev., 2010)

(untitled) - Coquerel, Y.; Rodriguez, J. (Eur. J. Org. Chem., 2008)

(untitled) - Wallace, D. J. (Tetrahedron Lett., 2003)

(untitled) - Courtot, P.; Kinastowski, S.; Lumbroso, H. (Bull. Soc. Chim. Fr., 1964)